Marketing Support of Small Family Businesses in The Agricultural Sector in Turkey on a Confidence Game - Kızıltuğ, Tuğçe; Dağıstan, Erdal (Turkish Journal of Agriculture - Food Science and Technology, 2021)
It is an important issue for small family businesses, which cannot keep up with the development of technology, you maintain their current position in the competition market and to increase their share of efficiency. Small family businesses meet a need about 80% of food production. Withdrawg these enterprise from the market may bring about a sudden drop in food supply. The aim of this study is to demonstrate to providing marketing training to small family businesses, how farmers can increase skills, production and profitability. Realization of these expectations will be possible with the support of big business or the public. In this study, using the game theory, possible strategies between two players (project founder and farmer) were taken into consideration and the gains to be obtained at each stage were found. As a result, it was concluded that cooperating with the investment institution and the farmer who received the training would increase the profit. This result is underlie of trust, cooperation and organization. Thus, while the production increases, the shortage of qualified personnel will decrease and contribution to employment will be provided. It will also contribute to overcoming technology-related marketing problems.